Alternative construction materials: a point of view on energy reduction and indoor comfort parameters - Paul O. Awoyera; John Effiong; Vamsi Nagaraju; Md. Aminul Haque; Md Azree Othuman Mydin; Kennedy Onyelowe (Discover Sustainability)
Abstract The indoor comfort of occupied buildings has become essential, as it significantly affects the productivity and health of occupants. This review provides a comprehensive overview of air and thermal comfort studies in residential buildings using alternative materials. This study aims to provide the trends and the state of the research in this field, to summarize the optimization methods, and to offer a perspective on future studies. The results demonstrate that in comparison to traditional air conditioning systems, natural ventilation systems, and air purifying plants have the potential to reduce energy consumption and carbon emissions in buildings by up to 60%. Also, cross-laminated timber (CLT) buildings can achieve energy savings of up to 30% compared to conventional buildings due to their superior insulation properties and reduced thermal bridging. This review has provided highlights to help the building owners to promote a healthier environment, reduce energy consumption and achieve more comfortable indoor air quality. The study promotes incorporating innovative materials and use of natural ventilation systems, smart air conditioning systems and air purifying plants.